PENGARUH EMOTIONAL INTELLEGENCE TERHADAP KINERJA INDIVIDU - Sri Sulistyowati; Imam Setyawan (AKSES: Jurnal Ekonomi dan Bisnis, 2007)
One of the supporting factors of an organization’s success is by continuously improving their employee’s performance so that they can help the organization to be more competitive. His/her Intelligence Quotient (IQ), but also his/her Emotional Intelligence (EI) does not only measure an employee’s performance. It has to be emphasized that EI can sometime be more important than IQ. Based on that assumption, this research is aimed at finding the connection between Emotional Intelligence and performance. Regression analyses results indicate that not all hypotheses are statistically supported. In line with the theory of Goleman (2001), which says, that a person’s emotional quotient will positively affect his/her performance, regression analyses indicate the same. However, regression analyses for individual elements that made up the emotional quotient do not indicate the same. Out of five individual elements, only self-organization that proved to be positive and significant, whereas motivation and social skill are statistically having positive influence but not significantly. Theoretically, both motivation and social skill do have positive effects on performance. And statistical analyses for self-realization and empathy showed negative influences. Keywords: Emotional Intelligence (EI), individual performance